Zum Einzelhandel in einer sowjetischen Stadt. Beobachtungen und Überlegungen am Beispiel von Erevan (Armenische SSR) - Stadelbauer, Jörg (ERDKUNDE, 1976)
The inner-urban structure of Soviet retail trade is studied by taking Yerevan, the capital of the Armenian SSR, as an example. Concerning the distribution of shops in the city of Yerevan (fig.1), the main contrasts with Western cities are the existence of shops for daily needs, the minor concentration of central services and the lesser degree of agglomeration between lines of business similar in type. Thus a hierarchy of shopping centres is formed, which corresponds to the whole-urban hierarchy as indicated in theoretical literature on socialist urbanism. The interpretation of Armenian data on retail trade turnover shows little deviation from Soviet averages. How ever, taking into account per capita expenditures, one can conclude that as capital Yerevan is better supplied with goods than other Armenian cities and even better than rural regions. Besides the state and cooperative retail trade, there exists a private sector in the kolkhoz markets. The examination of the main kolkhoz market (fig. 2) shows the great importance of these institutions in supplying the population with fresh fruits and vegetables. A secondary hierarchy of retail trade results from these markets, in which historical and ethnic singularities survived in some tradition of former bazaars. The organized retail trade is a Russian and Soviet achievement which has suffered until the present from the disregard of services in the Soviet economic policies.